2012
DOI: 10.1371/journal.pone.0042412
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Human Age with Bloodstains by sjTREC Quantification

Abstract: The age-related decline of signal joint T-cell receptor rearrangement excision circles (sjTRECs) in human peripheral blood has been demonstrated in our previous study and other reports. Until now, only a few studies on sjTREC detection in bloodstain samples were reported, which were based on a small sample of subjects of a limited age range, although bloodstains are much more frequently encountered in forensic practice. In this present study, we adopted the sensitive Taqman real-time quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…Twin studies have estimated high heritabilities for various visible traits such as height 48 and facial morphology 49 . In addition, recent studies show that age prediction is possible from DNA specimens derived from blood samples 50,51 . But the applicability of these DNA-derived quasi-identifiers for identity tracing has yet to be demonstrated.…”
Section: Identity Tracing Attacksmentioning
confidence: 99%
“…Twin studies have estimated high heritabilities for various visible traits such as height 48 and facial morphology 49 . In addition, recent studies show that age prediction is possible from DNA specimens derived from blood samples 50,51 . But the applicability of these DNA-derived quasi-identifiers for identity tracing has yet to be demonstrated.…”
Section: Identity Tracing Attacksmentioning
confidence: 99%
“…The levels of ␦Rec-J␣ sjTRECs in blood can be quantified by real-time quantitative PCR in humans (Hazenberg et al, 2001), and it is largely accepted that ␦Rec-J␣ sjTRECs are surrogate markers for thymic function (Kong et al, 1999;Wysoczanska, 2008). Previous studies have demonstrated an age-related progressive decline in blood ␦Rec-J␣ sjTREC levels (Zubakov et al, 2010;Ou et al, 2011Ou et al, , 2012Cho et al, 2014), possibly echoing age-related thymic atrophy. The measurement of blood ␦Rec-J␣ sjTREC levels and other molecular biology-based methods, including analysis of mitochondrial DNA 4977 bp-fragment deletion (Baumer et al, 1994;Hsieh et al, 1994;Lee et al, 1994;Meissner et al, 1997), telomere DNA fragment shortening (Tsuji et al, 2002;Ren et al, 2009) and methylation levels at specific genomic loci (Akira et al, 1987), have been applied to predict the age of humans for forensic purposes.…”
Section: Introductionmentioning
confidence: 94%
“…A thorough review of methods for predicting phenotypes from genomic data is provided in [22]. Two studies show that age prediction is feasible from DNA information derived from blood samples [30,41]. Several genome-wide studies report the influence of genomic data on height [1], body mass index (BMI) [26], eye color [38], and facial shape [8,24].…”
Section: Related Workmentioning
confidence: 99%